ANALISIS DETERMINAN NILAI PERUSAHAAN PADA SEKTOR PERTANIAN DI BURSA EFEK INDONESIA - Rizky Shafira Hazaroh (2021)
The purpose of this study is to see the determinants of firm value, related to profitability variables which are measured using Return on Equity (ROE), Debt Policy is measured by Debt Equity Ratio (DER), Investment Decisions are measured by Price Earning Ratio (PER), and CSR is measured by Corporate Social Responsibility Disclosure Index (CSRDI). The population in this study are agricultural sector companies on the Indonesia Stock Exchange in 2016-2019. Obtained 8 samples of agricultural companies during the 4 years research period. Data analysis was carried out with Microsoft Excel 2019 and hypothesis testing with Panel Data Regression Analysis using the E-Views 10.0 program, with a significance level of 5%. This study shows the results that (1) profitability (ROE) does not significantly affect firm value (PBV), (2) debt policy (DER) does not significantly affect firm value (PBV), (3) investment decisions (PER) do not have significant effect on firm value (PBV), and (4) Corporate Social Responsibility (CSRDI) has a significantly negative effect on firm value (PBV).